2000
DOI: 10.1007/bf02491033
|View full text |Cite
|
Sign up to set email alerts
|

Highly-substituted benzhydrylamine resin: An alternative chromatographic support for ganglioside and neutral glycosphingolipid purification

Abstract: Benzhydrylamine resin (BHAR) is a copolymer of (sl',/rene-1% divinylbenzene) containing phenylmethylamine groups and commonly used as a solid support for peptide synthesis in organic solvents. We have demonstrated that a larger number of NH3 + groups distribu ted throughout the BHAR matrix improves bead solvation under more polar conditions. As this characteristic might allow this aminated-polymer to be used as a stationary phase for liquid chromatogra-ph~ a highly substituted BHAR (2.4 mmol.g 1 of amine group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These results indicate that the AMR support, to date used only for peptide synthesis, can be applied as a cationic resin for chromatography, as was previously reported for 2.4 mmol/g BHAR, another polystyrene-type resin that attaches phenylaminomethyl groups instead. This latter solid support presented similar efficiency in the fractionation of negatively charged gangliosides [5] or carbohydrates [6,7] if compared with commercial anion exchanger resins such as the dextran-based DEAESephadex A25 (Amersham Biosciences) or the quaternary ammonium-bearing polystirene-2% divinylbenzene-based AG1-X1 (Bio Rad Co.). Despite its comparatively low exclusion limit if compared, for instance, to those containing highly hydrophilic dextranor agarose (Sepharose)-type anion exchanger matrices, the presence of more reactive primary amino groups in the AMR structure can be advantageous since this basic function could be easily derived in order to obtain novel resin derivatives.…”
Section: Anion-exchange Chromatography With the 49 Mmol/g Amrmentioning
confidence: 97%
See 1 more Smart Citation
“…These results indicate that the AMR support, to date used only for peptide synthesis, can be applied as a cationic resin for chromatography, as was previously reported for 2.4 mmol/g BHAR, another polystyrene-type resin that attaches phenylaminomethyl groups instead. This latter solid support presented similar efficiency in the fractionation of negatively charged gangliosides [5] or carbohydrates [6,7] if compared with commercial anion exchanger resins such as the dextran-based DEAESephadex A25 (Amersham Biosciences) or the quaternary ammonium-bearing polystirene-2% divinylbenzene-based AG1-X1 (Bio Rad Co.). Despite its comparatively low exclusion limit if compared, for instance, to those containing highly hydrophilic dextranor agarose (Sepharose)-type anion exchanger matrices, the presence of more reactive primary amino groups in the AMR structure can be advantageous since this basic function could be easily derived in order to obtain novel resin derivatives.…”
Section: Anion-exchange Chromatography With the 49 Mmol/g Amrmentioning
confidence: 97%
“…Negatively charged gangliosides [5] and carbohydrates [6,7] have been successfully fractionated with highly substituted BHAR batches. This resin is indeed, the first developed exclusively for use in peptide synthesis but applied as solid support for anion-exchange chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Unless otherwise stated, peptides were analyzed in a C 18 Vydac column (4.6 x 150 mm, 300 Å pore size, 5 mm particle size) with the solvent systems A: H 2 O containing 0.1% TFA; and B: 90% MeCN in H 2 O containing 0.08% TFA. A linear gradient of 10-90% B in 54 min was applied at a flow rate of 2.0 mL min -1 and with detection at 210 nm.…”
Section: Analytical Hplcmentioning
confidence: 99%
“…We have previously demonstrated that very highly ammonium substituted BHAR batches (>1.5-2.0 mmol g -1 ) actually display improved swelling in polar solvents, including water. 16 These findings prompted us to initiate the evaluation of its use as ion exchange supports for purification of negatively charged disaccharides 17 and gangliosides 18 in aqueous solution. Some physicochemical characteristics of this type of cationic resin have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…This effort in improving the polymer solvation knowledge has also recently led us to demonstrate that benzhydrylamine-resin (BHAR) 12 , a phenylmethylamine group-containing copolymer of styrene-1%-divinilbenzene, so far used as the solid support for peptide synthesis, can be alternatively employed as a novel anion exchange resin for liquid chormatography 13,14 .…”
Section: Introductionmentioning
confidence: 99%